Rubber plantation impacts on antibiotic resistance genes in tropical groundwater - Guoyu Lan; Rui Sun; Tong Pang; Chuan Yang; Zhixiang Wu (Journal of Hydrology: Regional Studies)
Study region: Hainan island, China. Study focus: Uncovering the distribution and mechanisms of antibiotic resistance genes (ARGs) in groundwater is crucial for safeguarding public health and environmental sustainability. Despite this, the influence of land use on tropical groundwater ARG profiles remains a critical knowledge gap. Our study employs metagenomic sequencing to delve into the composition, diversity, and driving forces behind ARGs in Hainan's tropical rainforests and rubber plantations. New hydrologic insights for the region: Our findings reveal a startling contrast: the total abundance of ARGs in rubber plantations soars above that in tropical rainforests, yet no significant differences emerge in α or β diversity. We pinpoint β-Proteobacteria as the primary carriers of ARGs, with Burkholderiaceae bacterium standing out as the key species-level player. Our analysis further unveils that the bacterial community wields the greatest influence (68.5 %) on ARG abundance, while land use exerts a substantial direct impact (27.3 %) and an indirect influence (24.9 %) by shaping the groundwater environment and microbial ecology. Moreover, mobile genetic elements (MGEs) serve a pivotal indirect role (31.5 %) in ARG abundance, albeit without affecting diversity. These insights lays the groundwork for mitigating the dissemination of resistance genes and their potential harm to human health.